2018
DOI: 10.1016/j.neuroscience.2018.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Loss of IGF1R in Human Astrocytes Alters Complex I Activity and Support for Neurons

Abstract: The insulin/insulin-like growth factor 1 (IGF1) signaling pathways are implicated in longevity and in progression of Alzheimer's disease. Previously, we showed that insulin-like growth factor 1 receptor (IGF1R) and downstream signaling transcripts are reduced in astrocytes in human brain with progression of Alzheimer's neuropathology and developed a model of IGF1 signaling impairment in human astrocytes using an IGF1R-specific monoclonal antibody, MAB391. Here, we have established a novel human astrocyte-neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Depleting cholesterol in cultured neural cells impairs intracellular signaling responses to a variety of important hormones (Fukui, Ferris, & Kahn, ). This finding is in general agreement with research demonstrating that cholesterol rich lipid membrane domains are required for cultured cells to respond normally to insulin (Ratcliffe et al, ). Moreover, it was recently shown that the IR requires membrane sterol content for its kinase activity (Delle Bovi, Kim, Suresh, London, & Miller, ).…”
Section: Brain Insulin Receptor and Insulin Resistance In Diabetes Ansupporting
confidence: 92%
“…Depleting cholesterol in cultured neural cells impairs intracellular signaling responses to a variety of important hormones (Fukui, Ferris, & Kahn, ). This finding is in general agreement with research demonstrating that cholesterol rich lipid membrane domains are required for cultured cells to respond normally to insulin (Ratcliffe et al, ). Moreover, it was recently shown that the IR requires membrane sterol content for its kinase activity (Delle Bovi, Kim, Suresh, London, & Miller, ).…”
Section: Brain Insulin Receptor and Insulin Resistance In Diabetes Ansupporting
confidence: 92%
“…A few other recent studies have utilized this inhibitory approach to explore the role of IGF‐1 in regulating other aspects of astrocyte function. Antagonism of IGFR using a monoclonal antibody decreased the ability of astrocytes to protect neurons from oxidative stress (Genis et al, ; Ratcliffe et al, ).This study by Ratcliffe et al . also showed that inhibition of IGFR did not alter the neurotrophic support provided by astrocytes, as no change in neurite outgrowth was observed in neurons co‐cultured with IGFR deficient astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypoxia repressed the activities of IGF-1 signaling in zebrafish embryos [44, 45]. IGF-1 signaling in human astrocytes displayed the capacity to protect neurons from oxidative stress [46]. These pathophysiological processes had also been reported as the possible link between TBI and AD [47].…”
Section: Discussionmentioning
confidence: 99%